Narrativa crítico-reflexiva: desenvolvimento acadêmico frente a metodologia ativa e os impactos da pandemia - Carrijo, Guilherme Rodrigues (Universidade Federal de São Carlos, 2021)
At the end of the medical course, students must make a critical and reflective assessment of their development and difficulties encountered throughout their trajectory. This is how I describe each of the cycles existing in the UFSCar medical course with each of its peculiarities, the first cycle being a moment of adaptation and development of bases for those who will come, the second cycle the deepening of that knowledge already acquired and the third and last cycle, responsible for the refinement of technical-scientific skills to practice the profession. However, we will have a brief report of countless difficulties and anxiety managed in such a unique moment, the pandemic that started at the end of 2019, referring to SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2).
Critical-reflexive narrative: academic development against active methodology and the impacts of pandemic
Keywords: Educação; Graduação em Medicina; Internato de Medicina; Pandemia COVID-19.; Education; Graduation in Medicine; Medical School; Pandemic COVID-19; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM